Telomerase activity in human pleural mesothelioma. Issue 11 (1st November 1998) - Dhaene, Karl; Hübner, Roland; Kumar-Singh, Samir; Weyn, Barbara; Van Marck, Eric
Abstract : BACKGROUND: Gradual telomere erosion eventually limits the replicative life span of somatic cells and is regarded as an ultimate tumour suppressor mechanism, eliminating cells that have accumulated genetic alterations. Telomerase, which has been found in over 85% of human cancers, elongates telomeres and may be required for tumorigenesis by the process of immortalisation. Malignant mesothelioma is an incurable malignancy with a poor prognosis. The disease becomes symptomatic decades after exposure to carcinogenic asbestos fibres, suggesting the long term survival of pre-malignant cell clones. This study investigated the presence of telomerase in pleural malignant mesothelioma, which may be the target for future anti-telomerase drugs. METHODS: Telomerase activity was semi-quantitatively measured in extracts from 22 primary pleural mesotheliomas, two benign solitary fibrous tumours of the pleura, four mesothelioma cell lines, and six short term mesothelial cell cultures from normal pleura using a non-isotopic dilution assay of the telomeric repeat amplification protocol. RESULTS: Twenty of the 22 primary mesotheliomas (91%) and all tumour derived mesothelioma cell lines were telomerase positive. Different levels of enzyme activity were observed in the tumours of different histological subtypes. Telomerase activity could not be detected in the six normal mesothelial cell cultures or in the two mesotheliomas. Both benign solitary fibrous tumours showed strong telomerase activity. CONCLUSIONS: Telomerase activity is found in a high proportion of mesotheliomas and anti-telomerase drugs might therefore be useful clinically. The results are consistent with the hypothesis that telomerase activity may be a feature of carcinogenesis in mesotheliomas and possibly in many other cancers.